Investigation and Production of Thyme Essential Oil Nanoemulsion Using Chitosan-Zein Pickering Emulsion Method by Nano Spray Drying Mechanism - Haniyeh Nikbakht; Ahmad Rajaei; Mohamad Movahednejad (Biomechanism and Bioenergy Research)
Nowadays, emulsion plays a significant role in encapsulating nutrients and volatile essences. One of the new methods for emulsion production involves the use of nanoparticles. A novel approach in producing nanoparticles is through the utilization of spray drying nanoencapsulation. In this study, thyme emulsion produced by three methods (rotary, spray drying, and Tween 80) was investigated. The results of morphological analysis of chitosan-zein particles (produced by rotary and spray drying) using scanning electron microscopy (SEM) revealed that the powder obtained from spray drying exhibited some agglomerated and clumpy regions, while the image of the powder obtained from the rotary method showed a more homogeneous and uniform structure. Particle size measurements indicated that the largest particle size was observed in the emulsion produced using the nano spray drying nanoencapsulation device. The rheological behavior of the emulsions demonstrated an increase in shear stress with an increase in shear rate for all samples in this research.